(untitled) (Studia Poliana, 2018)
Eudaimony and destiny.- Almost all the classical theories on ethics place man’s objective as his search for happiness. This ideal is based on nature. Medieval thinkers, considering man as a person, came to the conclusion that he is called t o a transcendental destiny; however, because they continued to use the classical ideal of happiness as a conceptual model, they created quite a few difficulties: self-transcendence and self-fulfillment are opposing models. L. Polo, on the other hand, proposes a non-naturalist anthropology that considers each person as destined to transcendence.